2020
DOI: 10.1177/0194599820926137
|View full text |Cite
|
Sign up to set email alerts
|

Alternations of Blood Pressure Before and After OSA Surgery

Abstract: Objective To investigate the changes of blood pressure (BP) on patients with obstructive sleep apnea/hypopnea syndrome (OSA) before and after upper airway surgery. Design Case series with chart review. Setting Tertiary academic medical center. Subjects and Methods Patients with OSA who underwent upper airway surgery were enrolled. We retrospectively investigated the nighttime and daytime BP before and at least 3 months after OSA surgery. Paired t test was used to compare the changes of BP before and after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…28 Reduction of internal carotid artery intima-media thickness was additionally observed in patients with moderate/severe OSA who received nasal surgery and UPPP. 29 Furthermore, our previous studies showed the effects of OSA surgery on improving the quality of life, 30,31 blood pressure, 32 metabolic profiles, 33 ophthalmologic microstructures, 34 baroreflex function, 35 as well as brain microstructures in functional magnetic resonance imaging and systemic inflammation biomarkers. 36 Current studies that discuss the cardiovascular outcomes in patients with surgical intervention only prove that these surgical treatments may provide benefits in some cardiovascular end points.…”
Section: Discussionmentioning
confidence: 99%
“…28 Reduction of internal carotid artery intima-media thickness was additionally observed in patients with moderate/severe OSA who received nasal surgery and UPPP. 29 Furthermore, our previous studies showed the effects of OSA surgery on improving the quality of life, 30,31 blood pressure, 32 metabolic profiles, 33 ophthalmologic microstructures, 34 baroreflex function, 35 as well as brain microstructures in functional magnetic resonance imaging and systemic inflammation biomarkers. 36 Current studies that discuss the cardiovascular outcomes in patients with surgical intervention only prove that these surgical treatments may provide benefits in some cardiovascular end points.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether a longer follow‐up period may generate different outcomes. Third, it is essential for evaluating the value of any OSA treatment via investigating the cardio‐ and cerebrovascular outcomes of the patients 31,32 . Thus, further MISS MLS studies for patients with OSA in this field should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is essential for evaluating the value of any OSA treatment via investigating the cardio-and cerebrovascular outcomes of the patients. 31,32 Thus, further MISS MLS studies for patients with OSA in this field should be conducted. Finally, no restrictions on the publish date were set.…”
Section: Literature Appraisals and Methodologymentioning
confidence: 99%